A new aza-crown macrocyclic fluorescent chemosensor (N3O2 donor atoms) for magnesium ions in aqueous ethanol solution. (12th January 2023) - Khanbabai, Fariba; Azadbakht, Reza; Koolivand, Mostafa
Abstract : A new N3 O2 aza-crown macrocyclic ligand (L ) bearing two fluorophore naphthalene moieties was synthesized and characterized by IR, 1 H and 13 C NMR, DEPt-135, HSQCGP, and microanalysis as well as by mass spectrometry. Abstract : A new N3 O2 aza-crown macrocyclic ligand (L ) bearing two fluorophore naphthalene moieties was synthesized and characterized by IR, 1 H and 13 C NMR, DEPt-135, HSQCGP, and microanalysis as well as by mass spectrometry. Comparative studies on the effect of various metal cations such as Cr(iii ), Cu(ii ), Cu(i ), Zn(ii ), Cd(ii ), Pb(ii ), Na(i ), Ni(ii ), Co(ii ), Ba(ii ), Fe(ii ), Fe(iii ), Al(iii ), La(iii ), Au(iii ), Mg(ii ), Cs(i ), Ca(ii ), Hg(ii ), K(i ), Mn(ii ) and Ag(i ) on the fluorescence of L were investigated in aqueous ethanol. The macrocycle was found to be a sensitive and selective fluorescent chemosensor for Mg 2+ . The binding constant value was established as 1.36 × 10 5 M −1 along with 1 : 1 stoichiometry for Mg 2+ –L . The detection limit was 2.51 × 10 −8 M with a rapid response time. Chemical inputs of Mg 2+ and Fe 3+ ions satisfy the conditions of an INHIBIT molecular logic gate.